1998
DOI: 10.1111/j.1600-0404.1998.tb07373.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor neurone disease in South Estonia Diagnosis and incidence rate

Abstract: The current study evaluated the diagnostic standards of MND and epidemiological markers of MND in Estonia. A total of 108 patients were referred to the University Hospital from 1986 to 1995 with the first suggested diagnosis or final diagnosis of amyotrophic syndrome, amyotrophic lateral sclerosis (ALS), progressive bulbar paralysis (PBP) or progressive muscular atrophy (PMA). In addition neurologists of the region and the National Society of Neuromuscular disorders were contacted. Some 94 patients satisfied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These factors are likely to exert their influence in all the regions of the world, albeit not in a uniform manner, either in relation to the chronology and intensity of their action. On this basis, it might be possible to explain the delay, observed in Sardinia, in the appearance of the phenomenon, its more precocious evidence in some regions and the stability of the findings noticed in other regions, for ALS (36,37,45,46,(50)(51)(52) as well as for MND (53,54).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…These factors are likely to exert their influence in all the regions of the world, albeit not in a uniform manner, either in relation to the chronology and intensity of their action. On this basis, it might be possible to explain the delay, observed in Sardinia, in the appearance of the phenomenon, its more precocious evidence in some regions and the stability of the findings noticed in other regions, for ALS (36,37,45,46,(50)(51)(52) as well as for MND (53,54).…”
Section: Discussionmentioning
confidence: 85%
“…However, the increase in life expectancy does not fully explain the changes in ALS incidence. On this basis, it might be possible to explain the delay, observed in Sardinia, in the appearance of the phenomenon, its more precocious evidence in some regions and the stability of the findings noticed in other regions, for ALS (36,37,45,46,(50)(51)(52) as well as for MND (53,54). Some authors (18,24,49) pointed out that the increase in the incidence rates is higher than expected, considering the mere ageing of the general population.…”
Section: Discussionmentioning
confidence: 88%
“…There was a 34-year study [38] and 4 studies of 20 to 22 years [22, 26, 33, 41]. Most studies, however, were conducted using 5-year [14, 29, 30, 43, 47, 48] or 10-year intervals [16, 19, 20, 32, 39, 42, 44]. The most frequently used data collection method was medical records review (n = 16) [13, 19, 22, 3134, 3740, 42, 4446, 48], followed by ALS registries (n = 11) [14, 1618, 20, 21, 23, 27, 30, 35, 49], surveys (n = 5) [15, 17, 18, 21, 25, 2730, 43, 45, 47], and databases (n = 5) [24, 26, 36, 41, 47].…”
Section: Resultsmentioning
confidence: 99%
“…In most of the longer-term studies, the entire study duration was divided into 2 periods covering longer intervals. Overall, 12 of 21 (57%) studies reported stable incidence rates over time [14, 16, 19, 22, 27, 32, 34, 35, 39, 41, 44, 46]; 5 reported increases in rates [20, 26, 33, 38, 40], and 4 reported highly variable rates over time [13, 24, 29, 42]. Two studies evaluated changes in incidence over time but compared an updated 1-year [15] or 5-year analysis [43] with previous publications excluded from the review (as older, related studies).…”
Section: Resultsmentioning
confidence: 99%
“…For the remaining six articles, a graphical reading of the figure of age-specific incidence was performed to obtain rates 4 , 33 , 35 , 52 , 53 , 59 . The demographic structure of the study population was fully available in 25 cases, 6 , 8 , 10–14 , 37 , 38 , 40 , 41 , 43–50 , 55 , 57 , 58 , 61 , 64 , 65 and in four additional studies the number of subjects for the youngest age groups (0-18) was re-calculated based on national census data 3 , 42 , 51 , 66 . For the other studies ( n = 12), the structure of the population under study was retrieved from national demographic databases 4 , 33–36 , 52–54 , 56 , 59 , 62 , 63 …”
Section: Resultsmentioning
confidence: 99%